A Study on the Performance Indicators of Malaysia's Stock Market During COVID-19 Pandemic - Chia, Zhe Yie; Kek, Sie Long (Enhanced Knowledge in Sciences and Technology, 2024)
The emergence of COVID-19 has caused Malaysia to implement various policies in response to the increasing number of infections. Movement Control Orders (MCO) have affected stock prices in Malaysia. FTSE Bursa Malaysia Kuala Lumpur Composite Index (FBMKLCI), which is a proxy to measure the performance of Malaysia’s stock market, hit its lowest record at 1219.72 points during the second day of MCO. Stock prices are affected by financial and non-financial performance indicators. Gross domestic product, consumer price index, industrial production index and exchange rate are financial indicators. The unemployment rate, number of COVID-19 cases and number of COVID-19 deaths are non-financial indicators. The monthly data from April 2020 to April 2022 is observed and analysed. Thus, the impact of the performance indicators on the stock market is identified using multiple linear regression analysis, and the relationship between Malaysia’s stock market and performance indicators during the COVID-19 pandemic is determined using the Granger causality test. The multiple linear regression analysis proves that the exchange rate, unemployment rate, and COVID-19 deaths negatively correlated with the FBMKLCI. The Granger causality test shows a unidirectional Granger relationship between CPI and FBMKLCI, verifying CPI is a valuable indicator for predicting the future stock price. Overall, the non-financial indicators are not recommended in forecasting future stock.